DIRECT in vitro REGENERATION OF CASTOR BEAN PLANTS (Ricinus communis) USING EPICOTYLS (2019)
regeneration protocol for castor bean plant (Ricinus communis) was successfully developed using epicotyl sections obtained from in vitro seedlings.